Full-range strain monitoring of rockbolts using the xCell Hydra instrumentation system - Vallati, O.; Reich, C.; Weaver, S. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The xCell Hydra system represents a new generation of instrumented ground support technology that integrates fibre Bragg grating (FBG) sensing into rockbolts to provide continuous, high-resolution measurements of axial strain along the reinforcement element for the entire capacity of the bolt. Traditional instrumentation methods in underground support, such as surface-mounted gauges or pointdisplacement transducers, are constrained by limited measurement range, spatial resolution and installation complexity. In contrast, the xCell Hydra system embeds an array of ruggedised FBG sensors within a helical groove along the bolt shaft, enabling distributed, multi-point, high-range strain measurement with minimal impact on mechanical performance and improved cable management. The technology is designed to be compatible with any threaded bar or bolt intended to be fully or partially embedded in resin or grout. Once installed, the instrumented bolt provides detailed strain measurements at each FBG sensor location, allowing operators to monitor load transfer, identify zones of high demand, and assess consumed capacity over time. During loading, each FBG sensor responds to local bolt deformation through wavelength shifts that are converted to engineering strain using a calibrated transfer function. This provides high-fidelity insight into bolt behaviour across the full loading regime, including elastic response, yield onset, load redistribution along the bolt length, and plastic deformation. This capability is especially valuable in caving operations, where large, rapidly evolving deformations demand reliable insight into support performance as the cave propagates and ground conditions deteriorate. Other applications in caving operations include asset monitoring, rehabilitation and ground support optimisation. The xCell Hydra technology has been applied to Sandvik’s Posimix bolts. Laboratory investigation results demonstrate excellent linearity, low noise and stable performance, highlighting the suitability of FBG-instrumented bolts for demanding underground environments. The paper first reviews current instrumented bolts described in the literature and their limitations. It then introduces the Hydra technology, explains the basics of FBG measurement principles, and reports the laboratory testing program undertaken to validate the approach.